The Role of Local Economic Development on Small, Medium and Micro Enterprises: Array - Mokoena, Sipho Kenneth (Acta Universitatis Danubius. Administratio, 2020)
This article aims at exploring the role of Local Economic Development (LED) in reshaping the economy of South Africa through the promotion of Small, Medium and Micro Enterprises (SMMEs) in local government. This paper is built on the post 1994 South African government concept of grassroots initiatives and community participation. With local government being viewed as a sphere of government, this meant that it is allocated a range of roles and responsibilities with respect to economic and social development. Therefore, the objective of the paper is to examine how the LED has contributed to reshape the grass root economy of South Africa. The research design used in this article was a mixed method approach. In the qualitative method, data were collected by means of an extensive review of government and public documents, academic books and articles. In terms of the quantitative method, SMME entrepreneurs in the Mbombela Local Municipality of the Mpumalanga Province, South Africa (SA) completed self-administered questionnaires. The findings point to the fact that South Africa needs to make the SMMEs environment conducive and favourable for business purposes. LED does contribute positively towards the growth of the economy of South Africa.